2017
DOI: 10.1111/jgs.15142
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Follow‐Up for Older Adults Discharged to Home from the Emergency Department: A Pragmatic Randomized Controlled Trial

Abstract: A scripted telephone call from a trained nurse to an older adult after discharge from the ED did not reduce ED or hospital return rates or death within 30 days. Clinicaltrials.gov identifier: NCT01893931z.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 45 publications
4
73
1
7
Order By: Relevance
“…Six studies, three randomized, reported hospitalization as a dichotomous outcome . Overall, there was no intervention effect for the randomized studies (relative risk [RR] = .96; 95% CI = .51‐1.83; Figure ), but the CI was wide, and intervention effects varied significantly (Q = 5.4; P = .07; I = 63%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies, three randomized, reported hospitalization as a dichotomous outcome . Overall, there was no intervention effect for the randomized studies (relative risk [RR] = .96; 95% CI = .51‐1.83; Figure ), but the CI was wide, and intervention effects varied significantly (Q = 5.4; P = .07; I = 63%).…”
Section: Resultsmentioning
confidence: 99%
“…When considered together, the randomized studies reporting ED return visit(s) as a dichotomous outcome found no effect on ED return visit(s) (RR = 1.13; 95% CI = .94‐1.36; Figure ) . A single low ROB study (n = 345) found that a multi‐strategy intervention that used all three key components led to an increased risk of ED return visit(s) at 30 days .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…47,48 The most intensive discharge follow up is a hospital at home programme. 47,48 The most intensive discharge follow up is a hospital at home programme.…”
Section: What Can the Ed Do?mentioning
confidence: 99%